MODELS OF BAY REINFORCED CONCRETE ELEMENTS RESISTANCE AT ACTION OF CYCLE PERMANENT SIGN HIGH LEVEL FORCES (Academic journal Industrial Machine Building Civil Engineering, 2018)
The reinforced concrete span beam structures work with small, middle and large shear spans under the action of cyclic loads of high levels is investigated. It is established that researches of physical models development of bending reinforced concrete elements fatigue resistance to the cyclic action of transverse forces and calculation methods on its base are important and advisable due to following features of said load type: the nonlinearity of deformation, damage accumulation in the form of fatigue micro- and macrocracks, fatigue destruction of materials etc. The key expressions of the concrete endurance limits definition (objective strength), longitudinal reinforcement, anchoring of longitudinal reinforcement, which consists the endurance of whole construction are determined. Also the role and the features of influence of vibro-creep deformations on the change mechanics of stress-strain state of concrete and reinforcement of research elements are investigated.
Keywords: endurance; cyclic load; fatigue destruction